2020
DOI: 10.48550/arxiv.2001.08879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broken symmetries and Kohn's theorem in graphene cyclotron resonance

Jordan Pack,
B. Jordan Russell,
Yashika Kapoor
et al.

Abstract: The magnetoplasmon spectrum of Landau level transitions in hexagonal boron nitrideencapsulated graphene is explored via infrared transmission magnetospectroscopy, as a function of the filling factor at fixed magnetic field. As the lowest Landau level occupancy is increased from half-filling, a non-monotonic progression of multiple cyclotron resonance peaks is observed, with a single peak evolving into four peaks and back to two, all with linewidths of order 0.5 meV. This provides a novel window on the interpla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, Russell et al [35] have reported a direct signal of manybody effects on CR in high-mobility hBN-encapsulated monolayer graphene; see also ref. [36]. They observed significant variations of resonance energies over a finite range of filling factor ν under a fixed magnetic field B; the point lies in extracting genuine Coulombic effects as a function of ν while controlling the running of the velocity factor with B.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Russell et al [35] have reported a direct signal of manybody effects on CR in high-mobility hBN-encapsulated monolayer graphene; see also ref. [36]. They observed significant variations of resonance energies over a finite range of filling factor ν under a fixed magnetic field B; the point lies in extracting genuine Coulombic effects as a function of ν while controlling the running of the velocity factor with B.…”
Section: Introductionmentioning
confidence: 98%